Comprehensive Analysis and Literature Review of Green Marketing in Indonesia: Trends, Methods, and Challenges - Indira Tyas Widyastuti; Desman Hidayat; Aditiya Hermawan (Komunitas Dosen Indonesia, 2024)
The objective of this study is to conduct a comprehensive review and synthesis of green marketing research within the Indonesian context, employing a literature review methodology that analyzes ten selected articles indexed in the Scopus database, all published between 2021 and 2023 as part of open-access publications. The majority of these studies utilize a quantitative approach, focusing predominantly on Java Island, which may limit the findings' generalizability to other regions in Indonesia. The industries examined range from fashion and textiles to agriculture, showcasing the broad applicability of green marketing principles. The respondent profiles vary, including customers, companies, and industry experts, providing a multifaceted understanding of green marketing dynamics. Despite generally positive relationships identified between green marketing practices and various outcomes, inconsistencies, particularly concerning the role of trust, highlight the complexity of this factor in green marketing. Some studies identify trust as a significant mediator in green marketing effectiveness, while others do not find substantial evidence supporting this relationship, indicating a need for further investigation. These mixed results underscore the necessity for more research, especially utilizing qualitative or mixed-method approaches, and expanding beyond Java Island to gain deeper insights. The findings from this review serve as a foundational framework for future research in green marketing in Indonesia, offering critical insights into trends, methodological approaches, and diverse application contexts, thereby emphasizing the strategic importance of integrating environmental principles into business practices to enhance competitiveness and support sustainable economic growth. Understanding the role of trust and other mediators in green marketing can inform better strategies for fostering consumer confidence and encouraging environmentally responsible purchasing behaviors. This study highlights current trends and identifies gaps in the literature, paving the way for more nuanced and regionally diverse research, thus contributing to the broader discourse on sustainable marketing practices in Indonesia.